2009
DOI: 10.1093/heapro/dap028
|View full text |Cite
|
Sign up to set email alerts
|

Social capital does matter for adolescent health: evidence from the English HBSC study

Abstract: Social capital has grown out of the recognition that health-related behaviours are shaped and constrained by a range of social and community contexts and that the ways in which an individual relates to social networks and communities has important effects on their health and well-being. Given the strong and complex inequalities that exist in adolescent health at both the national and international levels, social capital, acting a protective factor (or asset), may help reduce poor outcomes. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
93
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 12 publications
10
93
2
3
Order By: Relevance
“…These results are similar to the results from other studies [2,30]. Family support undoubtedly represents a key element for children’s health, as a perception of belonging to the family is related with health behaviors in childhood [41]. Also, after achieving independence in the 1990s, Lithuania moved from socialism to capitalism.…”
Section: Discussionsupporting
confidence: 88%
“…These results are similar to the results from other studies [2,30]. Family support undoubtedly represents a key element for children’s health, as a perception of belonging to the family is related with health behaviors in childhood [41]. Also, after achieving independence in the 1990s, Lithuania moved from socialism to capitalism.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have shown that involvement in the neighbourhood during adolescence and high social capital in rural residents are highly associated with consumption of fruit and vegetables (12,13) . In addition, there is adequate evidence for a link between social network structure, social capital and patterns of obesity (14)(15)(16) .…”
mentioning
confidence: 99%
“…At its best, school can strengthen determinedly and systematically youngsters' health resources and increase their health capital. It will reflect in youngsters' ability to live as citizens who cherish and promote their health (Morgan and Haglund 2009).…”
Section: Discussionmentioning
confidence: 99%